Structural Dynamics of Lytic Polysaccharide Monooxygenase during Catalysis - Filandr, Frantisek; Kavan, Daniel; Kracher, Daniel; Laurent, Christophe V F P; Ludwig, Roland; Man, Petr; Halada, Petr (Biomolecules, 2020)
Lytic polysaccharide monooxygenases (LPMOs) are industrially important oxidoreductases employed in lignocellulose saccharification. Using advanced time-resolved mass spectrometric techniques, we elucidated the structural determinants for substrate-mediated stabilization of the fungal LPMO9C from Neurosporacrassa during catalysis. LPMOs require a reduction in the active-site copper for catalytic activity. We show that copper reduction in NcLPMO9C leads to structural rearrangements and compaction around the active site. However, longer exposure to the reducing agent ascorbic acid also initiated an uncoupling reaction of the bound oxygen species, leading to oxidative damage, partial unfolding, and even fragmentation of NcLPMO9C. Interestingly, no changes in the hydrogen/deuterium exchange rate were detected upon incubation of oxidized or reduced LPMO with crystalline cellulose, indicating that the LPMO-substrate interactions are mainly side-chain mediated and neither affect intraprotein hydrogen bonding nor induce significant shielding of the protein surface. On the other hand, we observed a protective effect of the substrate, which slowed down the autooxidative damage induced by the uncoupling reaction. These observations further complement the picture of structural changes during LPMO catalysis.
Keywords: hydrogen/deuterium exchange mass spectrometry; lignin; Oxidative Stress; reaktivní formy kyslíku; Catalytic Domain; oxidative amino acid modification; oxidační stres; Catalysis; Mass Spectrometry; Mixed Function Oxygenases; Substrate Specificity; fungální proteiny; Neurospora crassa; Copper; Protein Binding; celulosa; peptide bond cleavage; Protein Conformation; Reactive Oxygen Species; měď; oxidoreduktasy; hmotnostní spektrometrie s elektrosprejovou ionizací; Lignin; Oxygen; kyslík; oxygenasy se smíšenou funkcí; lytic polysaccharide monooxygenase; substrátová specifita; katalytická doména; Cellulose; vazba proteinů; Hydrogen-Ion Concentration; reactive oxygen species; lignocellulose degradation; Spectrometry, Mass, Electrospray Ionization; Polysaccharides; polysacharidy; Fungal Proteins; koncentrace vodíkových iontů; Oxidoreductases; hmotnostní spektrometrie; katalýza; konformace proteinů